Persepsi Pasien Tentang Kualitas Pelayanan Perawatan Orthodontik - Magfira, Magfira; Samsualam, Samsualam; Yusriani, Yusriani (Wal'afiat Hospital Journal, 2022)
Improvement of services in accordance with the ability and willingness to pay is expected to increase the number of visits and as a form of equality in obtaining health services for the community. This study aims to determine the patient's perception of the quality of orthodontic treatment services at W'Art Dental Care Makassar. This research is an analytical survey with a descriptive design. The study population was orthodontic treatment patients at W'Art Dental Care, with the entire population as a sample of as many as 53 respondents. Data analysis used univariate analysis. The results showed that from a total of 53 respondents, most of them were female (94.3%), and were in the 26-31-year-old (45.3%) age group, with a higher education level (62.3%) and a profession. as a private employee (41.5%). Patients' perceptions of service quality in the Good category were 40 people (75.7%). The conclusion of this study is that most patients stated that orthodontic treatment services at W'Art Dental Care Makassar were in a suitable category. The suggestion, the administration, nurses, and doctors must maintain the quality of service that has been rated well by the patient